Burnout in teaching activity: evidence of a study involving higher education institutions - Sousa, Juliana Carvalho de; Oliveira, Agostinha Mafalda Barra de; Silva, Pablo Marlon Medeiros da; Brito, Lydia Maria Pinto (Revista de Administração da UFSM, 2020)
The present research has the objective of investigating a relationship of the social, institutional and emotional aspects with Burnout syndrome incidence in teachers of higher education institutions in the city of Mossoró, RN. We chose a descriptive, quantitative research, and descriptive and inferential statistics, using Pearson’s analysis as a statistical technique. A sample was attended by 103 teachers from three higher education institutions in the city of Mossoró. The results showed that among the investigated teachers, 43.7% had high levels of emotional exhaustion, 22.3% manifested levels of depersonalization, and 53.4% pointed of low professional achievement, generally revealing that 41% of respondents are a strong trend towards the development of a syndrome. Regarding correlations, among the analyzed aspects, all evidenced variables that showed a significant correlation. In this way, it can be inferred that the syndrome is multicausal.